ASPEK HUKUM REKAM MEDIS - Ratna Winahyu Lestari Dewi (Perspektif, 2003)
Medical Record has very important function. It is called ALFRED, stands for Administrative Value, Legal Value, Financial Value, Research Value, Education Value and Documentary Value. Medical Record will be needed as an administrative instrument in a prosecution case, as a financial function to calculate treatment expenses, as a research and education function, it is also has other function as a documentation device and further, has law aspects: administration, civil and criminal law.